If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = -5(8x + -7) + 5(-4 + 3x) Reorder the terms: 15 = -5(-7 + 8x) + 5(-4 + 3x) 15 = (-7 * -5 + 8x * -5) + 5(-4 + 3x) 15 = (35 + -40x) + 5(-4 + 3x) 15 = 35 + -40x + (-4 * 5 + 3x * 5) 15 = 35 + -40x + (-20 + 15x) Reorder the terms: 15 = 35 + -20 + -40x + 15x Combine like terms: 35 + -20 = 15 15 = 15 + -40x + 15x Combine like terms: -40x + 15x = -25x 15 = 15 + -25x Add '-15' to each side of the equation. 15 + -15 = 15 + -15 + -25x Combine like terms: 15 + -15 = 0 0 = 15 + -15 + -25x Combine like terms: 15 + -15 = 0 0 = 0 + -25x 0 = -25x Solving 0 = -25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '25x' to each side of the equation. 0 + 25x = -25x + 25x Remove the zero: 25x = -25x + 25x Combine like terms: -25x + 25x = 0 25x = 0 Divide each side by '25'. x = 0 Simplifying x = 0
| 18x^2-2y^4=0 | | -3.8+4.6+1.6x+7=x+3.9 | | 3x-8=x-2 | | 5x-20+x=70 | | 3x-7x+15+6x=41 | | x-6(x-1)=7(3+x) | | 0.6(15d+20)-6(18d-12)=38 | | -3.5+4.6+1.6x+7=x-3.9 | | -12=z-3 | | -2x+2+6=-3 | | 5.3=-6+x | | -2(-c-20)=-2c-20 | | 6(7x-2)=72 | | 56=8-8(1+7v) | | 6m+6=30 | | 1.5(6c-18)+0.75(8c+32)=78 | | 3x+16=100 | | =x^3-4x^2-25x+100 | | 2c+6c=81 | | -14+3a=10a | | 4x-9=28x+9 | | 4m+3m=42 | | 3(2x-14)=6(x-2) | | 8-2s-3-s=-4+18 | | 17*5=x | | 29+15x=-x-3 | | 65=5-8x+2x | | 3x-8=4y+4 | | x-0.10=63 | | (2/3)n+8=0.5n+2 | | 2g+12=28 | | x^2-7x-294=0 |